Severe maternal morbidity and near misses in tertiary hospitals, Kelantan, Malaysia: a cross-sectional study - Mohd Noor Norhayati; Nik Hussain Nik Hazlina; Zaharah Sulaiman; Mohd Yacob Azman (BMC, 2016)
Abstract Background Severe maternal conditions have increasingly been used as alternative measurements of the quality of maternal care and as alternative strategies to reduce maternal mortality. We aimed to study severe maternal morbidity and maternal near miss among women in two tertiary hospitals in Kota Bharu, Kelantan, Malaysia. Methods A cross-sectional study with record review was conducted in 2014. Severe maternal morbidity and maternal near miss were classified using the new World Health Organization criteria. Health indicators for obstetric care were calculated and descriptive analyses were performed using SPSS version 22.0. Results In total, 21,579 live births, 395 women with severe maternal morbidity, 47 women with maternal near miss and two maternal deaths were analysed. The severe maternal morbidity incidence ratio was 18.3 per 1000 live births and the maternal near miss incidence ratio was 2.2 per 1000 live births. The maternal near miss mortality ratio was 23.5 and the mortality index was 4.1 %. The process indicators for essential interventions were almost 100.0 %. Haemorrhagic disorders were the most common event for severe maternal morbidity (68.6 %) and maternal near miss (80.9 %) and management-based criteria accounted for 85.1 %. Conclusions Comprehensive emergency care and intensive care as well as overall improvements in the quality of maternal health care need to be achieved to substantial reduce maternal death.